FirstLight III: rest-frame UV-optical spectral energy distributions of simulated galaxies at cosmic dawn - Ceverino, Daniel; Klessen, Ralf S.; Glover, Simon (Monthly notices of the Royal Astronomical Society, 2019)
ABSTRACT. Using the FirstLight data base of 300 zoom-in cosmological simulations we provide rest-frame UV-optical spectral energy distributions of galaxies wit